β-Actin: Not a Suitable Internal Control of Hepatic Fibrosis Caused by Schistosoma japonicum - Zhang, Beibei; Wu, Xiaoying; Liu, Jiahua; Song, Langui; Song, Qiuyue; Wang, Lifu; Yuan, Dongjuan; Wu, Zhongdao (Frontiers in Microbiology, 2019)
Schistosomiasis japonica is a significant health problem that leads to morbidity and mortality of humans. It is characterized by hepatic granulomatous response and fibrosis caused by eggs deposition in the liver. β-actin, a traditional housekeeping gene, is widely used as an internal control to normalize gene and protein expression. However, β-actin expression can fluctuate upon the treatment with pharmacological agents or under some physiological and pathological conditions. In this study, we found that the expressions of both β-actin mRNA and protein increased significantly with hepatic fibrosis formation after 6 weeks infection with S. japonicum and kept high level during the progression of hepatic fibrosis, while the levels of β-Tubulin and GAPDH remained stable. The dynamic change β-actin was similar with the profibrogenic factors, including α-SMA, Collagen I, Collagen III. We employed immunofluorescence staining and further showed that the expression level of β-actin was positively correlated with α-SMA. What’s more, there was a positive correlation between the level of β-actin mRNA and the content of hydroxyproline in liver. This study provides evidences that β-actin is variable and unsatisfied for application as an internal control in hepatic fibrosis induced by S. japonicum infection.